Chromenopyrazole, a Versatile Cannabinoid Scaffold with in Vivo Activity in a Model of Multiple Sclerosis - Morales, Paula; Gomez-Canas, Maria; Navarro, Gemma; Hurst, Dow P.; Carrillo-Salinas, Francisco J.; Lagartera, Laura; Pazos, Ruth; Goya, Pilar; Reggio, Patricia H.; Guaza, Carmen; Franco, Rafael; Fernandez-Ruiz, Javier; et al. (Journal of medicinal chemistry, 2016)
A combination of molecular modeling and structure activity relationship studies has been used to fine-tune CB2 selectivity in the chromenopyrazole ring, a versatile CB1/CB2 cannabinoid scaffold. Thus, a series of 36 new derivatives covering a wide range of structural diversity has been synthesized, and docking studies have been performed for some of them. Biological evaluation of the new compounds includes, among others, cannabinoid binding assays, functional studies, and surface plasmon resonance measurements. The most promising compound [43 (PM226)], a selective and potent CB2 agonist isoxazole derivative, was tested in the acute phase of Theiler's murine encephalomyelitis virus-induced demyelinating disease (TMEV-IDD), a well established animal model of primary progressive multiple sclerosis. Compound 43 dampened neuroinflammation by reducing microglial activation in the TMEV.